Transformer thermal model of the disk coils with non directed oil flow - Yaqoob, Mansoor Taha (2013)
A power transformer is a static piece of apparatus with two or more windings which, by electromagnetic induction, transforms a system of alternating voltage and current into another system of voltage and current usually of different values and at same frequency for the purpose of transmitting electrical power. The temperature of disk coil has a close relation with the transformer age. In oil immersed transformers, oil guides are applied generally to enhance the cooling effects for disc windings. In some cases disk windings without oil guides are used. Non directed oil flow of a disk transformer in this model is non-guided by the oil flow natural circulation (thermally driven). The model is focus to investigate the temperature rise in the oil-filled transformer windings. An iterative solution is required to solve the equation to find the oil velocities, change in the oil temperature rise after each disk coil that passing through it, and disk temperature. The concept in all disks coil is the same because no block washer for each group (pass) to control of the oil flow as directed oil flow. Pressure decrease with increase the total number of coil disk or high of coil is effecting the frication and gravitation acceleration. As a disk temperature is very sensitive to the changes of the variables, so designing a suitable parameter for a single power transformer is very important. Matlab software that a good way to solve the iterate equations and modeling disk transformer where the result is nearly accurate.